An approach to ecosystem-based management in maritime spatial planning process. (1st June 2017) - Ansong, J.; Gissi, E.; Calado, H.
Abstract: Sustainable development is the framing concept assuring that resources are exploited while maintaining the ability of these natural resources to provide for future generations. With human dependence on marine resources increasing, Ecosystem-Based Management (EBM) has been identified as a suitable approach to ensure sustainable development. In order to achieve this, the core principles and elements of EBM should be operational in the maritime/marine spatial planning (MSP) process to ensure that human activities in marine space are ordered to attain ecological, economic and social objectives. However, policies from various states and organizations sometimes do not set a clear precedence for translating principles of EBM and present different and complex approaches to an ecosystem-based marine spatial planning (EB-MSP). Again, a feasible methodology for EBM to be operational in MSP is still vague. This paper therefore presents results from a survey and review of MSP initiatives in Europe, Asia and the Americas. Results showed that essential MSP steps and elements such as adaptive management, setting of planning boundaries, understanding and analysing the ecosystem and future conditions are not fully operational. This paper focuses on a methodology for EB-MSP and gives recommendations on how to ensure that EBM is operational at each stage of an MSP process. It stresses the importance of setting planning boundaries beyond jurisdictional borders to consider bio/eco-regions and cover near-shore waters, the need to have a cross-sector integration, understanding the ecosystem through having an ecosystem service perspective and having a legal framework to ensure that results from monitoring and evaluating of plans are adapted through review and revision. Highlights: A methodology for ecosystem-based marine spatial planning. How to ensure that ecosystem-based management is operational at each stage of an MSP process (recommendations). A step by step approach embedded on the MSP process. Challenges and specific features of EBM in MSP.